Analisis Keterampilan Proses Sains Peserta Didik Pada Materi Ikatan Kimia Kelas X SMA Negeri 6 Madiun - Agustyna Widyaningrum; Rudiana Agustini (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2021)
This study aims to describe the science process skills of students on each indicator and to find out the average percentage of students who have a science process skill level category (high, medium, and low) chemical bonding material with the POGIL learning model. This research uses pre-experimental research with the one group pretest posttest research desaign. The data collection techniques used were observation and assessment tests. The data analysis technique used paired T-Test (SPSS version 16) and N-gain Score. The results showed that the data were normally distributed, namely the Sig.> 0.05. Paired Sample T-Test obtained Sig. (2-tailed) of 0.00, which means that the test is <0.05. So it can be concluded that the POGIL learning model has a significant effect on the science process skills of students. The science process skills of the five indicators, the classification indicator has the highest average posttest score percentage of 96.21% and the observing indicator has the lowest average posttest score percentage of 71.21%. Science process skills have increased from the average results of the pretest and posttest values, namely from 65.76% to 88.41%. The improvement of science process skills is in the moderate category with the N-gain Score index of 0.67.